Transmission-blocking activity of a chitinase inhibitor and activation of malarial parasite chitinase by mosquito protease. - Shahabuddin, M (1993)
During development in the mosquito midgut, malarial parasites must traverse a chitin-containing peritrophic matrix (PM) that forms around the food bolus. Previously Huber et al. [Huber, M., Cabib, E. & Miller, L. H. (1991) Proc. Natl. Acad. Sci. USA 88, 2807-2810] reported that the parasite secretes a protein with chitinase activity, and they suggested that parasite chitinase (EC 3.2.1.14) plays an important role in the parasite's egress from the blood meal. We found that allosamidin, a specific inhibitor of chitinase, completely blocked oocyst development in vivo and thus blocked malaria parasite transmission. Addition of exogenous chitinase to the blood meal prevented the PM from forming and reversed the transmission-blocking activity of allosamidin. Using exogenous chitinase, we also found that the PM does not limit the number of parasites that develop into oocysts, suggesting that the parasite produces sufficient quantities of chitinase to penetrate this potential barrier. In addition, we found that treatment of parasite chitinase with a diisopropyl fluorophosphate-sensitive trypsinlike protease from the mosquito midgut or endoproteinase Lys-C increased its enzymatic activity. These results suggest that malaria parasite has evolved an intricate mechanism to adapt to the PM and the protease-rich environment of the mosquito midgut.